Muscle glycogen content modifies SR Ca2+ release rate in elite endurance athletes - Gejl, K. D.; Hvid, L. G.; Frandsen, U.; Jensen, K.; Sahlin, K.; Ortenblad, N. (Medicine & Science in Sports & Exercise, 2014)
Purpose: The aim of the present study was to investigate the influence of muscle glycogen content on sarcoplasmic reticulum (SR) function and peak power output (Wpeak) in elite endurance athletes.